Genome-Wide Association Mapping for Cold Tolerance in a Core Collection of Rice (Oryza sativa L.) Landraces by Using High-Density Single Nucleotide Polymorphism Markers From Specific-Locus Amplified Fragment Sequencing - Song, Jiayu; Li, Jinqun; Sun, Jian; Hu, Tao; Wu, Aiting; Liu, Sitong; Wang, Wenjia; Ma, Dianrong; Zhao, Minghui (Frontiers in Plant Science, 2018)
Understanding the genetic mechanism of cold tolerance in rice is important to mine elite genes from rice landraces and breed excellent cultivars for this trait. In this study, a genome-wide association study (GWAS) was performed using high-density single nucleotide polymorphisms (SNPs) obtained using specific-locus amplified fragment sequencing (SLAF-seq) technology from a core collection of landraces of rice. A total of 67 511 SNPs obtained from 116 643 SLAF tags were used for genotyping the 150 accessions of rice landraces in the Ting’s rice core collection. A compressed mixed liner model was used to perform GWAS by using the high-density SNPs for cold tolerance in rice landraces at the seedling stage. A total of 26 SNPs were found to be significantly (P<1 × 10-7) associated with cold tolerance, they could explained phenotypic variations ranging from 26 % to 33 %. Among them, two QTLs were mapped closely to the previously cloned/mapped genes or QTLs for cold tolerance. A newly identified QTL for cold tolerance in rice was further characterized by sequencing, real time-polymerase chain reaction, and bioinformatics analyses. One candidate gene, i.e., Os01g0620100, showed different gene expression levels between the cold tolerance and sensitive landraces under cold stress. We found the difference of coding amino acid in Os01g0620100 between cold tolerance and sensitive landraces caused by polymorphism within the coding domain sequence. In addition, the prediction of Os01g0620100 protein revealed a WD40 domain that was frequently found in cold tolerance landraces. Therefore, we speculated that Os01g0620100 was highly important for the response to cold stress in rice. These results indicated that rice landraces are important sources for investigating rice cold tolerance, and the mapping results might provide important information to breed cold-tolerant rice cultivars by using marker-assisted selection. Key words: Rice (Oryza sativa L.) landraces, Ting’s rice core collection; Cold tolerance; Genome-wide association study; Candidate gene; Seedling stage